NEW DEVICE FOR RECONSTRUCTION AND BALCONY FEATURES OF FORMATION OF SETTLEMENT OF MODELS - and and (Municipal economy of cities. Series: «Economy science», 2013)
The necessity of a joint analysis of structures arranged in the reconstruction of buildings and balconies of the building itself. The expediency of the use of the deformed scheme of buildings operated in difficult geological conditions during the formation of their computational models.